Antibiotic purification by using zeolites adsorbent - Nur Munirah, Abd Wahab (2009)
Effective separation and purification of antibiotic has been an important issue in the pharmaceutical industries. A novel antibiotic adsorption has been developed in biotechnology to achieve high efficiency and economical separation processes. Application in separation and purification processes often used the ability of zeolites and other molecular sieves to exclude larger molecules to enter the pores and admit smaller ones. In this study, three types of zeolites which are Y, Beta and ZSM-5 have been used to study the effect of their performance on the antibiotic purification. The zeolite is used as an immobilized metal ion affinity stationary phase for antibiotic purification. The adsorption of Rifampicin antibiotic using zeolites was studied. Rifampicin adsorbance was analyzed by using UV/VIS Spectrophotometer. The zeolite Beta is recognized to have highest adsorption capacity compared to zeolite Y and ZSM-5. The adsorption capacity of Rifampicin depends on their types of structure, pore size of the zeolite, surface area as well as pore volume of the zeolite. The effect of pH on adsorption capacity was studied at four different pHs, namely 5, 7, 8, and 9. It is found that the adsorption capacity is the highest at pH 8 which is the nearest to the pKa of Rifampicin. Increase in pH lower than pKa value result in increasing adsorption capacity. But,increase in pH higher than pKa value results decreasing adsorption capacity. This is postulate due to the electrostatics repulsion between antibiotic molecules and the surface of adsorbent. Lastly, it can be concluded that the most efficient zeolite is Beta at pH 8.The adsorption isotherms data on Rifampicin are fitted to the Langmuir model.